2021
DOI: 10.3390/jcm10051023
|View full text |Cite
|
Sign up to set email alerts
|

Functional Condition of Patients after Unilateral Hip Arthroscopy in the Process of FAI—Femoroacetabular Impingement: A Case–Control Study and Preliminary Report

Abstract: Introduction: Femoroacetabular impingement is a commonly recognized condition among people with hip pain. Aim: The aim of this study was to assess how arthroscopy and physiotherapy treatment influenced the quality of life and functional condition of patients after arthroscopic femoroacetabular impingement (FAI) surgery. Materials and methods: We examined 19 people for the study and included 12 (6 men and 6 women). Their mean age was 40.1 ± 9.7 years. Manual and digital goniometers were used for the range of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It has been shown that the pathology of FAI causes a significant difference in hip range of motion in the planes of flexion, abduction, extension, external rotation (ER) and internal rotation (IR). 22,23 Clinicians should consider contralateral hip FAI morphology or range of motion limitations when clearing an athlete in this category. 22 The recommended passing criteria is pain-free active and passive range of motion within five degrees of the contralateral hip in all planes with consideration to any contralateral hip morphology.…”
Section: Criteria 1: Range Of Motionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that the pathology of FAI causes a significant difference in hip range of motion in the planes of flexion, abduction, extension, external rotation (ER) and internal rotation (IR). 22,23 Clinicians should consider contralateral hip FAI morphology or range of motion limitations when clearing an athlete in this category. 22 The recommended passing criteria is pain-free active and passive range of motion within five degrees of the contralateral hip in all planes with consideration to any contralateral hip morphology.…”
Section: Criteria 1: Range Of Motionmentioning
confidence: 99%
“…22,23 Clinicians should consider contralateral hip FAI morphology or range of motion limitations when clearing an athlete in this category. 22 The recommended passing criteria is pain-free active and passive range of motion within five degrees of the contralateral hip in all planes with consideration to any contralateral hip morphology. In this situation, clinicians can reference previously established normative ranges of motion for the hip joint bearing in mind the influences of factors such as age, gender, and race.…”
Section: Criteria 1: Range Of Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical examination typically reproduces pain upon specific patterns of hip movement: flexion, adduction and internal rotation (FADIR, impingement test), and/or flexion, abduction, and external rotation (FABER test). 1 , 2 , 3 Additional diagnostic workup includes a loss or marked reduction in hip ROM between the affected and unaffected contralateral joint, 2 , 4 , 5 , 6 or in the case in which symptoms are experienced bilaterally, significant restriction in the available ROM from the acceptable normative ranges. 7 Owing to the typical location of these deformities, movements such as flexion, adduction, and internal rotation 10 , 11 , 12 , 13 , 8 , 9 often are reduced with abduction and external rotation being spared.…”
mentioning
confidence: 99%